PENERAPAN MODEL INKUIRI TERBIMBING BERBASIS LESSON STUDY TERHADAP PEMAHAMAN KONSEP DAN KETERAMPILAN KOMUNIKASI MAHASISWA PADA MATAKULIAH FISIOLOGI HEWAN DAN MANUSIA UNIVERSITAS NEGERI MALANG: IMPLEMENTATION OF INQUIRY MODEL BASED ON LESSON STUDY ON THE UNDERSTANDING OF THE CONCEPT AND SKILLS OF STUDENTS COMMUNICATION IN THE PHYSIOLOGY OF ANIMAL AND HUMAN UNIVERSITAS NEGERI MALANG - Nosi Qadariah; Murni Saptasari; Sri Endah Indriwati (Jurnal Psikologi Jambi, 2021)
Introduction The purpose of education is directed in accordance with developments in technology, information, and communication. Students are expected to have skills and skills. Understanding concept is the basis for achieving various 21st century. The results of observations indicate understanding of student’s concepts and communications skills is low. The right solution to solve this problem is the application of guided inquiry based on Lesson Study (LS).Method Classroom action research method using a qualitative descriptive approarch based on lesson study in the form of plan, do, see stages.Results The results showed that the implementation of inquiry learning syntax in the first cycle was 98% and increased in the second cycle to 100%. The application of inquiry can increase student’s understanding of concepts by a percentage of 71,75 in the first cycle and increased to 81,3 in the second cycle. Communication skills with a classical average of 81,2 in the first cycle and increased to 84,95 in the second cycle.Conclusions and Recomendations Criteria for the implementation of the inquiry model and lesson study are very accomplished and can improve student’s understanding of concepts and communications skills.Keywords inquiry learning, understanding of concept, communication skills, Lesson Study (LS) ABSTRAK Pendahuluan Tujuan pendidikan diarahkan sesuai dengan perkembangan teknologi, informasi, dan komunikasi. Mahasiswa diharapkan memiliki kecakapan dan keterampilan. Pemahaman konsep merupakan dasar untuk mencapai berbagai keterampilan abad 21. Keterampilan komunikasi merupakan salah satu kecakapan yang harus dimiliki di abad 21. Hasil observasi menunjukkan pemahaman konsep dan keterampilan komunikasi mahasiswa masih rendah. Solusi yang tepat untuk menyelesaikan masalah ini adalah penerapan Inkuiri Terbimbing berbasis Lesson Study (LS). Metode Penelitian tindakan kelas dengan menggunakan pendekatan deskriptif kualitatif berbasis lesson study berupa tahapan plan, do, see. Hasil Penelitian menunjukkan bahwa keterlaksanaan sintaks pembelajaran inkuiri pada siklus I sebesar 98% dan meningkat pada siklus II menjadi 100%. Penerapan inkuiri dapat meningkatkan pemahaman konsep mahasiswa dengan persentase 71,75 pada siklus I dan meningkat menjadi 81,3 pada siklus II. Keterampilan komunikasi dengan rata-rata klasikal sebesar 81,2 pada siklus I dan meningkat menjadi 84.95 pada siklus II. Kesimpulan dan Saran Kriteria keterlaksanaan model inkuiri dan lesson study sangat terlaksana serta dapat meningkatkan pemahaman konsep dan keterampilan komunikasi mahasiswa. Kata Kunci pembelajaran inkuiri, pemahaman konsep, keterampilan komunikasi, Lesson Study (LS).